Variable past participles in Portuguese perfect constructions. (2nd May 2019) - Schwenter, Scott A.; Hoff, Mark; Christodulelis, Eleni; Pflum, Chelsea; Dauphinais, Ashlee
Abstract: Some Portuguese verbs have two past participle forms: one regular (stem + -do ), and the other irregular (often identical to the first person singular present indicative). Per grammars, the perfect auxiliaries ter / haver take regulars, while irregulars appear with passive/adjectival ser / estar . To test these claims, we analyzed naturally-occurring data from Brazil (twentieth century) and Portugal (nineteenth and twentieth). We coded 1077 tokens from 21 verbs for ten predictors and performed mixed-effects logistic regressions in R. Irregulars appear with ter/haver 54% overall and in 68% of cases from Portugal. Our results demonstrate that past participle choice is determined by the interaction of several linguistic factors. While lexical verb is the most significant predictor of participle selection, verbs with irregular participles identical to the first person singular present indicative occur in the irregular significantly more than other verbs. We conclude that analogical processes underpin the variation. This conclusion allows us to adjudicate between competing accounts of past participle choice in Portuguese.